Pengaruh Motivasi Belajar dan Kecerdasan Interpersonal Terhadap Prestasi Belajar IPS SMP Negeri di Kecamatan Cilandak Jakarta Selatan - Risan Risan (Hikmah: Journal of Islamic Studies, 2017)
The research was conducted at the state SMP in Sub-district Cilandak South Jakarta by survey research method. Students of research respondent are 50 people, selected based on simple random sampling and proportional sampling. The instrument uses questionnaire of learning achievement as the dependent variable, while the questionnaire instrument of learning motivation and interpersonal intelligence were used as the independent variable. Research instrument is validated by product moment correlation formula, whereas reliability is measured by Alpha Cronbach formula. Research method used in this research is Explanatory Survey Method. Data analysis technique used in this research is Regression Analysis Modelto find out the influence ofindependent variable with the dependent variable. Statistical test using t-test. Data analysis using correlation and regression technique (simple and plural). From the result of the study found that : (1) there is a significant influence between learning motivation on learning achievement of IPS at the state SMP in Sub-district Cilandak South Jakarta (r=0,834 and Ŷ = -27.268 + 0,219X1). (2) there is significant influence between interpersonal intelligence on learning achievement of IPS in the state SMP in Sub-district Cilandak South Jakarta (r = 0,834 dan Ŷ = -27.268 + 0,197X2). (3) there is significant influence between Learning Motivationand Interpersonal Intelligence together with Learning Achievement of IPS in the state SMP in Kecamatan Cilandak South Jakarta. Keywords: Learning motivation, Interpersonal intelligence, Prestasi Belajar Penelitian dilaksanakanpada SMPNegeridi Kecamatan Cilandak Jakarta Selatan, dengan metode penelitian survei. Responden penelitian siswa berjumlah 50 orang, dipilih berdasarkan teknik acak sederhana (simple random sampling) dan proporsional sampling. Instrumen menggunakan angket prestasi belajar sebagai variabel terikat, sedangkan instrument angket motivasi belajar dan angket kecerdasan interpersonal sebagai variabel bebas. Instrumen penelitian divalidasi dengan rumus korelasi product moment, sedangkan reliabilitas diukur dengan rumus Alpha Cronbach. Metode penelitian yang digunakan adalah Explanatory Survey Method, Teknik analisis data yang digunakan dalam penelitian ini adalah Model Analisis Regresi untuk mengetahui pengaruh dari variabel bebas dengan variabel terikat. Uji statistika menggunakan uji-t. Analisisdatamenggunakanteknikkorelasidanregresi(sederhana & jamak).Dari hasil penelitian ditemukan bahwa : (1) terdapat pengaruh yang berarti antara motivasi belajar terhadap prestasi belajar IPS pada SMP Negeri di kecamatan Cilandak Jakarta Selatan (r = 0,834 dan Ŷ = -27.268 + 0,219X1). (2) terdapat pengaruh yang berarti antara kecerdasan interpersonal terhadap prestasi belajar IPS SMP Negeri di Kecamatan Cilandak Jakarta Selatan (r = 0,834 dan Ŷ = -27.268 + 0,197X2). (3) terdapat pengaruh yang berarti antara Motivasi Belajar dan Kecerdasan Interpersonal bersama-sama terhadap Prestasi Belajar IPS SMP Negeri di Kecamatan Cilandak Jakarta Selatan. (r = 0,834 dan Ŷ = -27.268 + 0,219X1 + 0,197X2). Kata Kunci: Motivasi Belajar, Kecerdasan interpersonal, Learning achievement